Preceptoria em Residência em Fisioterapia: percepções e vivências pedagógicas - Piñeiro, Paula Nunes (2024)
The training of human resources for the health area, with the Unified Health System as the organizer, has been considered an important element to strengthen and provide assistance to the population. In this sense, residencies in different sectors of the health area have been gaining ground due to the increase in proposals in institutions. Among the main actors that make up the residency programs, the preceptor stands out, who performs teaching-assistance supervision, organizing the learning process and guiding students. In this sense, the general objective of this study was to identify the perception of preceptors of Residency Programs in the Professional Area of Physiotherapy regarding their role in the process of training specialists and, as specific objectives, to investigate the available evidence on preceptorship in health in Brazilian scientific publications; to identify the perception of preceptors who work in Residency Programs in Physiotherapy and correlate it with the legal guidelines in official documents regarding the role of preceptorship in health; to determine whether preceptors have training. The publications were selected based on the following descriptors: preceptorship in residency; preceptorship in health; mentoring in health. After selection in the Lilacs, Medline and Coleciona SUS databases, 27 publications that addressed the review theme were selected, and the following themes were identified: Competencies and duties of the preceptor; Pedagogical training in preceptorship; and Challenges and experiences in the exercise of preceptorship. In the exploratory part of the research, the following guiding question was taken: Do preceptors, in the position in which they are inserted, understand their role and have pedagogical training to contribute to the training of specialists in Physiotherapy Residencies? The invited participants were preceptors linked to the active Physiotherapy Residency Programs of the State University of Londrina and the State University of Western Paraná. Data collection was carried out using a structured form in Google Forms®, which took place from August 1, 2023 to December 31, 2023. Objective data were described and subjective data were subjected to content analysis. Twenty-three preceptors participated, 57% of whom were linked to Unioeste and 43% linked to UEL residency programs. The majority of them were female, aged 49 or over, with varied specializations including master's, doctorate and lato sensu degrees. 72% of the participants exercise preceptorship in their areas of specialization. The data from the exploratory study were presented in two articles. The first addressed the Perception of Preceptors of Residency Programs in the Professional Area of Physiotherapy, in which the importance of the preceptor was unanimously recognized among the responses. However, there is a worrying gap between the perception of preceptors and the guidelines established by the MEC, highlighting the need for greater familiarity and engagement with these documents. The second article addressed the Training, preparation and pedagogical performance of preceptors of physiotherapy residencies and highlighted several challenges related to the exercise of preceptorship, including the lack of pedagogical preparation, the lack of incentives from institutions, the absence of teaching and evaluation methodologies for residents, work overload and lack of time to fulfill all the requirements of the pedagogical proposal, among others. The results of the studieswere able to highlight the urgency of regulating several aspects related to the practice of preceptorship.